Husband's Social Support for Mothers With Postpartum Depression After Giving Birth to Their First Child - Dian Mustika Sari; Eko Hardi Ansyah (Psikologia : Jurnal Psikologi, 2015)
This study aims to provide an overview of social support her husband with postpartum depression in mothers postpartum first child and the impact of social support provided to the mother's husband. Social support is in the form of emotional support, the support award, instrumental support and informative support. The method used in this research is using qualitative exploratory study the two subjects who had a husband and wife with postpartum depression after giving birth first child with wife aged 21-28 years. Determination of the subjects in this study using purposive sampling technique and is located in several places according to the agreement of the subject and significant others. Data collection methods used were observation method using anecdotel record with the observation that social support indicators husband and interview methods are equipped with general guidance interview. The results showed that each subject provide social support her husband with different forms of support for marriage influenced by the subject. The effect of the second wife of the study subjects also differ on the subject of the first wife can get through 25 days postpartum depression after giving birth, while the second subject can get through 40 days postpartum depression after giving birth. Factors support from significant others and coping also affect maternal postpartum depression can get through the second wife of the research subjects.